Edukasi dan Upaya Deteksi Penyakit Tidak Menular Melalui Pemeriksaan Kesehatan - Masroni; Sholihin; Nazmi, Annisa Nur; Damayanti, Fransiska Erna; Munif, Badrul; Rudiyanto, Rudiyanto; Kusumawati, Diana; Indriani, Ninis; Izzah, Ukhtul; Ariyani, Anita Dwi; Anitarini, Fany; Hermanto, Andrik (Jurnal Pengabdian Masyarakat (JUDIMAS), 2025)
Non-Communicable Diseases (NCDs) often undetected because they have no symptoms and there no complaints. Usually found at an advanced stage, so it will be difficult to cure and ends in disability and death. This situation creates large costs for sufferers, families and the state. NCDs can be prevented by controlling risk factors. Increasing public awareness and concern for NCD risk factors very important in controlling NCDs. Counseling, examinations and surveillance of NCD risk factors are forms of health efforts to prevent an increase in the prevalence of non-communicable diseases. The activity of the undergraduate nursing and professional nursing lecturer's service program which is integrated with Thematic KKN is in the form of providing information to the community about the risk factors for non-communicable diseases (PTM), followed by examining the risk factors for non-communicable diseases in the community in the Grogol Village area, Giri Banyuwangi District. The reason for choosing the location based on the Mojopanggung Community Health Center's annual report, it shows that the prevalence of non-communicable diseases such as hypertension, DM, gout is always included in the 10 most types of disease every year. Therefore, it is very important to provide education regarding hypertension, gout and blood sugar to the public to prevent complaints and bad impacts, so that it will extend life expectancy and increase the productivity of residents who experience these diseases.